Exploring the Impact of Academic Vocabulary on L2 Writing Proficiency among University Students - Muhammad Tanveer Aslam; Sadia Akhtar (JELLL, 2025)
The acquisition of academic vocabulary plays a pivotal function in shaping the writing proficiency of 2nd language (L2) learners, in particular on the university level in which academic discourse is essential. This study looks at how well students can write in a second language when they know a lot of words for teaching. Writing in 2d language is very hard because it needs to use the right words, follow the rules of grammar, and make sense. The study aims to investigate the volume to which academic vocabulary affects students’ capacity to assemble meaningful, well-organized, and contextually suitable written texts in English A blended-strategies approach become adopted, combining each quantitative and qualitative records. The participants were undergraduate students enrolled in English language programs at a public-sector college. Quantitative data were collected using standardized academic vocabulary stage tests, while qualitative statistics were acquired through the analysis of student writing samples. The writing samples have been checked for how many different words they use, how well they follow the rules of grammar, how well they connect their ideas, and how they match the style of academic writing. Possible – We use math tools like correlation and regression to see how long the words are that teachers use and how well students write. The findings imply a strong positive correlation between students’ academic vocabulary information and their writing proficiency. Students with a broader educational vocabulary verified greater clarity, coherence, and complexity in their writing. Moreover, the choice of academic words helped to improve the quality of writing in L2. The study concludes that academic vocabulary Is a key predictor of L2 writing success and recommends that language instructors region more emphasis on academic lexical development in ESL and EAP (English for academic functions) publications. Future research may similarly discover the position of discipline-specific vocabulary and its affect on writing performance across different academic fields. Keywords: Academic Vocabulary , L2 Writing Proficiency , Vocabulary Knowledge , ESL Learners , English for Academic Purposes (EAP) , Writing Performance